ASSESSING ISLAMIC INFORMATION QUALITY ON THE INTERNET: A CASE OF INFORMATION ABOUT HADITH - Abdul Karim, Nor Shahriza; Hazmi, Norzelatun Rodhiah (Malaysian Journal of Library and Information Science, 2005)
The convenience of the Internet in providing access to a vast amount of information about Islam is no longer deniable even among students and faculties in Islamic Studies. The Internet has been regularly used by this category of people to find information about Islam. On the other hand, the issue pertaining to the quality of the information made available on the Internet is very transparent. In Islam, it is indeed very important that any fatwa and any scholarly works on Islam should be based on original and reliable sources of information. The question is if the Internet is continued to be one of the major source of information and reference for Islamic Scholars, how do they assess its quality? How do they justify its use? In what manner do they utilize the information? Using a case study approach with qualitative data gathering technique, this study was conducted to understand the use, perceptions, and opinions of several postgraduate students and faculty members in a faculty of Islamic Studies at one of the public university in Malaysia, pertaining to information about Hadith on the Internet. The findings indicated that almost all participants have referred to the Internet to get information about Hadith. The analysis of the interviews has revealed the purpose of use, method of assessment used and the underlying issues involved as perceived by the participants.